Research on seismic activity and seismic structural characteristics of the Shandong region - Linhai Lu; Zhenghao Liu; Hanwen Zhang; Chaojun Wu; Jiecheng Sun; Xianfeng Ma; Dingyi Zhou; Han Han; Haojin Zhang; Rui Li (Scientific Reports)
Abstract This study provides a comprehensive analysis of seismic activity and structural characteristics in Shandong Province, China, with a focus on identifying seismic belts and potential epicentral zones critical for regional seismic safety. A detailed database was developed, integrating regional seismicity statistics, earthquake distribution patterns, significant geotectonic movements, and recent neotectonic activities. The results reveal that seismic activity in Shandong is heterogeneously distributed, with moderate to strong earthquakes predominantly associated with active fault zones and exhibiting zonal clustering. Earthquakes are generally shallow, occurring within the middle to upper crust, with historical destructive events averaging a focal depth of 19 km, while recent minor seismic events average 14.9 km in depth. These activities span North China Plain and Tan-Lu Seismic Statistical Areas. Projections indicate sustained or heightened seismic activity over the next century, with the potential for earthquakes up to magnitude 5. The geological framework is dominated by Luxi Fault Block and Tan-Lu Fault Zone, characterized by episodic uplift and subsidence driven by neotectonic movements. The prevailing horizontal tectonic stress regime supports the likelihood of strike-slip faulting as the predominant mechanism.